Pengaruh Kepemimpinan Transformasional Kepala Desa dan Disiplin Kerja Aparatur Desa Terhadap Peningkatan Kinerja Aparatur Desa di Kantor Geuchik Drien Rampak Kecamatan Johan Pahlawan Kabupaten Aceh Barat - Hajar, Siti; Alfansyah, Farit (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This study aims to use a quantitative approach to the phenomena that occur at the Geuchik Drien Rampak Office, Johan Pahlawan District, West Aceh Regency. The data method used in this study is the Total Sampling technique with a sample of 24 Village Apparatus. The data used are Primary data and Secondary data. The data analysis techniques that will be used are Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Analysis Test, Hypothesis Testing using SPSS22 Software and Determination Coefficient. The results of this test state that the Influence of Transformational Leadership of Village Heads and Work Discipline of Village Apparatus on Improving the Performance of Village Apparatus at the Geuchik Drien Rampak Office, Johan Pahlawan District, West Aceh Regency.